Developing a Blueprint for a Technology-mediated Approach to Translation Studies - Alonso, Elisa; Calvo, Elisa (Meta, 2015)
As Austermühl (2001) put it over a decade ago, the use of information and communication technologies is a fait accompli in the lives of today’s translators. Translation Studies (TS) have traditionally contemplated technologies only as supporting tools for translation practice, and translators’ tools have not enjoyed consideration as decisive actors in TS. Hence, their impact has been somehow underrepresented in the discipline. In the light of well-established translation paradigms (linguistic, functional, cognitive, sociological), we analyze the role played by technology. Most TS approaches are artifactual, this meaning that a rather simplistic and outdated distinction is made between translator minds and the tools they use. This paper proposes an instrumental approach to technologies within TS. In this, cohesive and mutual merging between translators and their technologies, both field-specific and generic tools lead us towards a concept that goes beyond purely linguistic or anthropocentric translation notions. A trans-human translation theoretical modeling is proposed to revisit TS paradigms in the context of the Information Society era. The trans-human translation closes the loop initiated by the fragmentation and dehumanization of first translation technologies, and envisages a stimulating future for translators, where they will use technological and social extensions in a creative and critical way.